Exploring Acceptance of Agro-Biomass as Innovative Solution for Heating in Rural Areas in Romania - Ibolya Török; Enikő Mátyus; Tihamér-Tibor Sebestyén; Carmen Păunescu; Kinga Xénia Havadi-Nagy (Resources)
This paper aims to examine what can predict the adoption of agro-biomass as an innovative heating solution in rural areas. It explores the social acceptance of agro-biomass such as agriculture byproducts for heating in a rural context. The objectives are threefold: (1) to examine if there is a causal relationship between awareness and knowledge of agro-biomass applications for heating and intention to adopt this solution; (2) to investigate the extent to which perceived local drivers as well as barriers associated with agro-biomass utilization influence the intention to adopt this heating solution; and (3) to determine if knowledge about agro-biomass energy use, as well as political barriers to agro-biomass adoption for heating, play a mediating and/or moderating role in the established causal relationships. This paper uses primary data collected from rural residents located in different geographic areas in Romania. The 673 valid responses were analysed through multiple regression and mediation and moderation tests. The results confirm that awareness, knowledge, and perception of local drivers and of political barriers are positive predictors of intention to adopt agro-biomass as an innovative solution for heating. They also confirm the mediating role of knowledge and the moderating role of political barriers in the established relationships.